Schwannoma of the anterior maxillary vestibular submucosa: A case report. Issue 1 (January 2017) - Shibata, Akio; Kimura, Masashi; Ohto, Hiroyuki; Yamada, Hiroki; Umemura, Masahiro
Abstract: Schwannomas (neurilemomas) are benign nerve sheath tumors that derive from proliferating Schwann cells. The most common intraoral site is the tongue, followed by the buccal or vestibular mucosa, palate, lip, and gingiva. Schwannomas are solitary, slow-growing, smooth-surfaced, encapsulated, and usually asymptomatic tumors. Their preoperative diagnosis is often difficult, and in the majority of cases, the diagnosis is confirmed by imaging studies and surgical excision with histological assessment. Here we report a rare case of schwannoma of the maxillary vestibular region with a predominantly Antoni A microscopic pattern in a 29-year-old male. The chief complaint was a painless, slow-growing swelling on the left anterior maxillary vestibular region. T2-weighted magnetic resonance imaging (MRI) revealed a mass with moderate-signal intensity in the periphery with a central area of high intensity with a clear smooth border, whereas the lesion appeared isointense to muscle on T1-weighted MRI. The patient was definitively diagnosed with schwannoma by histological evaluation of incisional biopsy material, and immunohistochemistry revealed that the tumor was diffusely positive for S-100. Thus, the tumor was excised, and the patient's prognosis was good. Precise knowledge of the clinical, radiological, and histological characteristics of schwannomas is critically important for its prompt diagnosis and treatment. To the best of our knowledge, we report a rare case of intraoral schwannoma of alveolar submucosa.